2022
DOI: 10.1186/s12967-022-03743-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of the size and methylation of chromosome 4qA-D4Z4 repeats in facioscapulohumeral muscular dystrophy by long-read sequencing

Abstract: Background Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant muscular disorder characterized by asymmetric muscle wasting and weakness. FSHD can be subdivided into two types: FSHD1, caused by contraction of the D4Z4 repeat on chromosome 4q35, and FSHD2, caused by mild contraction of the D4Z4 repeat plus aberrant hypomethylation mediated by genetic variants in SMCHD1, DNMT3B, or LRIF1. Genetic diagnosis of FSHD is challenging because of the complex procedures required. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Furthermore, a recent study by Hiramuki et al, 2022 tested a long-read sequencing-based approach, which allowed the authors to simultaneously analyze the D4Z4 methylation and size in FSHD patients. Additionally in this case, the authors found reduced global D4Z4 methylation levels in FSHD samples and provide precise insights into the pathological epigenetic status of D4Z4 locus [ 20 ]. Indeed, our results are consistent with all the aforementioned data and further support the applicability of DNA methylation assessment and 4q haplotyping to prioritize or exclude patients for FSHD diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent study by Hiramuki et al, 2022 tested a long-read sequencing-based approach, which allowed the authors to simultaneously analyze the D4Z4 methylation and size in FSHD patients. Additionally in this case, the authors found reduced global D4Z4 methylation levels in FSHD samples and provide precise insights into the pathological epigenetic status of D4Z4 locus [ 20 ]. Indeed, our results are consistent with all the aforementioned data and further support the applicability of DNA methylation assessment and 4q haplotyping to prioritize or exclude patients for FSHD diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with previous studies reporting similar observations [ 17 , 21 ]. In addition, the application of long read sequencing found comparable reduced D4Z4 methylation levels for both 4q and 10q in FSHD2 patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Caputo and colleagues [57,58] developed a protocol for methylation analysis of specific CpG residues using iMachine Learning (ML) algorithms to classify FSHD cases. Hiramuki et al , [59 ▪ ] applied long-read sequencing through a Nanopore CRISPR/Cas9-targeted resequencing to diagnose FSHD by simultaneous detection of D4Z4 repeat length and methylation status at the nucleotide level in FSHD patients. Erdmann et al [60] developed a methylation-based diagnostic workflow comprising a haplotype and high-throughput methylation profile analyses (FSHD-MPA).…”
Section: Resultsmentioning
confidence: 99%
“…Initial efforts to use nanopore sequencing for FSHD, struggled due to lack of read-depth in 4q derived D4Z4 arrays from genomic analyses (Mitsuhashi et al 2017). Development of strategies to enrich sequences of interest using Cas9-targeting has led to improved read-depth for regions of interest (Gilpatrick et al 2020), including the D4Z4 array associated with FSHD (Hiramuki et al 2022) Nanopore sequencing not only opens the door to the full sequencing of the D4Z4 array, but also allows determination of CpG methylation in the array, a critical aspect of genetic analysis for FSHD.…”
Section: Discussionmentioning
confidence: 99%